Topological Phase Transitions and New Developments 2018
DOI: 10.1142/9789813271340_0012
|View full text |Cite
|
Sign up to set email alerts
|

Realizing quantum materials with Helium: Helium films at ultralow temperatures, from strongly correlated atomically layered films to topological superfluidity

Abstract: This article provides an overview, primarily from an experimental perspective, of recent progress and future prospects in using helium to realize a range of quantum materials of generic interest, by "top-down" and "bottom-up" nanotechnology. We can grow model systems to realise new quantum states of matter, and explore key issues in condensed matter physics. In the language of cold atomic gases, two dimensional and confined 3 He and 4 He provide "quantum simulators", with the potential to uncover new emergent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 135 publications
0
6
0
Order By: Relevance
“…The properties of ideal Fermi and Bose gases are the starting points for the understanding of the low-temperature behaviour of a broad range of physical systems, including electrons in metals [1,2], the helium liquids [3,4] and systems of trapped gases [5]. Associated with these is interest in systems of lower dimensionality including graphene [6], helium films [7] and ultra-cold atoms in quasi-1d and quasi-2d traps [8].…”
Section: Introductionmentioning
confidence: 99%
“…The properties of ideal Fermi and Bose gases are the starting points for the understanding of the low-temperature behaviour of a broad range of physical systems, including electrons in metals [1,2], the helium liquids [3,4] and systems of trapped gases [5]. Associated with these is interest in systems of lower dimensionality including graphene [6], helium films [7] and ultra-cold atoms in quasi-1d and quasi-2d traps [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the successful design, fabrication, and use of a nanofabricated stepped-height sample container is the latest step into the microkelvin studies of topological mesoscopic superfluidity. The method enables the creation of hybrid nanofluidic devices by sculpture of the order parameter [34]. Future variations of such structures -combining the flexibility of confinement geometry with in situ tuneable boundary condition [33] -provide unprecedented versatility to study and harness the emergent topologically protected surface-, interface-, and edge-bound low-energy states [34,[57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Here we present a versatile nanofabricated stepped-height sample container for SQUID-based nuclear magnetic resonance (NMR) studies. In such a container, the state of the superfluid 3 He is tuned by confinement, which allows creating several essentially isolated volumes of superfluid within a single measurement platform [33,34]. Our container has nearly atomically smooth surfaces in five such "isolated" phasenucleation volumes, eliminating the heterogeneous nucleation.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of 4 He atoms deposited on solid substrates has been identified for many decades as a bosonic many-body problem that could exhibit a rich phase diagram including the possibility of dimensional crossover [1][2][3][4][5][6][7][8]. Graphite was first recognized as an ideal twodimensional substrate due to its exceptional homogeneity, [9] and extensive experimental [10,11] and theoretical studies [12][13][14] have demonstrated that under the right circumstances a superfluid He film can develop on the graphite surface.…”
Section: Introduction a Helium On Two-dimensional Materials: A Many-b...mentioning
confidence: 99%